Climate change, armed conflict, forced displacement, and epidemic-prone diseases: an exploratory study in northern Syria - Maia C. Tarnas; Naser Almhawish; Ruwan Ratnayake; Yasir Elferruh; Ibrahim Aladhan; MHD Bahaa Aldin Alhaffar; Aula Abbara (BMC Public Health)
Abstract Introduction Northern Syria is particularly vulnerable to the joint effects of climate change and conflict. This has contributed to numerous infectious disease outbreaks which disproportionately affect people who have been forcibly displaced. We aimed to assess the associations between environmental factors, conflict, displacement, and two types of epidemic-prone diseases in northern Syria: suspected respiratory infections and diarrheal diseases. Methods We used data from the Early Warning Alert and Response Network (EWARN) syndromic surveillance system between 2016 and 2023 on two suspected respiratory infections and five suspected diarrheal diseases. These cases were aggregated by disease type at the district-week level. For each disease type, we used a generalized additive model with a negative binomial probability distribution that accounted for several environmental variables (including precipitation, surface water, temperature, humidity, and vegetation), displacement, conflict events, total consultations, prior disease cases, seasonality, and spatial factors. Seasonal-trend decomposition with locally estimated scatterplot smoothing was also used to detect trends amidst seasonal fluctuations. Results Over 21 districts in 5 governorates, 8,774,734 suspected respiratory infections and 6,903,396 suspected diarrheal disease cases were reported. Proportionate morbidity for both disease types began increasing in late 2018 and early 2019 with fluctuations; this varied by governorate. Scaled mean temperature (SD: 11.59°C) was associated with decreased risk of respiratory infections (IRR: 0.92; 0.87-0.98) but increased risk of suspected diarrheal disease (1.06; 1.03-1.09) in the same week and up to 8 weeks and 4 weeks later, respectively. Precipitation exhibited similar contrasting risk patterns. Surface water and vegetation levels also corresponded to changes in disease transmission risk. The interaction between high levels of displacement and conflict was associated with increased risk for both, though suspected diarrheal diseases had a lower threshold for increased risk. Conclusions Conflict, environmental factors, forced displacement, and infectious diseases are inextricably linked in northern Syria. These findings can inform public health preparedness and anticipatory activities and policies that address the effects of climate change on infectious diseases. This is especially relevant as Syria enters a new geopolitical chapter following the fall of the Assad regime, with changing health needs, population movement, and new opportunities for health system recovery.